Penerapan Metode Preference Selection Index (PSI) Dalam Penerimaan Staff IT - Widya Indah Safitri; Mesran Mesran; Sarwandi Sarwandi (Bulletin of Informatics and Data Science, 2022)
In a company or agency, employees are one of the keys to success in achieving certain goals in the company. However, getting the right IT staff and in accordance with what the company or agency wants is certainly not easy. Therefore, to get employees who meet expectations and fulfill all stages carried out by the company, it is necessary to select the right employee candidates so that later it will produce competent IT staff in their fields. The Preference Selection Index (PSI) method is a method for solving multi-criteria decision making (MCDM). This method is useful when there is a conflict in determining the relative importance between attributes. From the results of the study, it was obtained that alternative A9 was the best alternative to be chosen as the company's IT staff with the highest score of 0.9624